ANALISIS STRATEGI PENGEMBANGAN KAWASAN AGROPOLITAN KABUPATEN NGANJUK - Tripitono Adi Prabowo (Trunojoyo University of Madura, 2015)
The aim in this study was to determine the development strategy of the region Agropolitan Nganjuk by knowing the internal factors and external factors that exist in Nganjuk. The method used in this research is SWOT analysis to identify the weaknesses, strengths, opportunities and challenges in the development of the area Agropolitan in Nganjuk so it can determine its development strategy. The results this study is the development strategy that can be used is divided into three stages: 1) Incubation, equating the vision of all stakeholders, 2) implementation, the implementation of development strategies that have been defined, 3) Exit Strategy, strategy development and renewal.